Pengaruh Kualitas Pelayanan dan Relationship Marketing terhadap Kepuasan Pelanggan PT. PLN (Persero) Unit Layanan Pelanggan Medan Helvetia - Eva Margareth Sarah; Niscaya Hia; Anggi Kristina Sinaga (Yayasan Literasi Sains Indonesia, 2025)
This study aims to determine the effect of service quality and relationship marketing on customer satisfaction at PT PLN (Persero) ULP Helvetia Medan. The effect of service quality and relationship marketing will be analyzed partially and simultaneously on customer satisfaction. The research method used is quantitative research. Data collection techniques using questionnaires distributed directly to customers of PT PLN (Persero) ULP Helvetia Medan with survey techniques. The sample in this study were 97 customers of PT PLN (Persero) ULP Helvetia Medan. The analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the research conducted show that the variables of service quality (X1) and relationship marketing (X2) have a significant effect on customer satisfaction (Y). So, it can be concluded that the effect of each variable simultaneously can be seen that the Fcount value is 77.993> Ftable 3.09 or sig. of 0.000 <0.05. The data is processed statistically using the SPSS program tool.